Hydrogen Production Based on Liquid Organic Hydrogen Carriers through Sulfur Doped Platinum Catalysts Supported on TiO2 - Chen, Ximeng; Gierlich, Christian H.; Schötz, Simon; Blaumeiser, Dominik; Bauer, Tanja; Libuda, Jörg; Palkovits, Regina (ACS Sustainable Chemistry & Engineering, 2021)
In order to move from a carbon-based energy system to a more sustainable one, focus is put on liquid organic hydrogen carrier (LOHC) systems for CO2-free hydrogen storage and release. In this study sulfur as a dopant for the Pt/TiO2 catalyst was identified to be a selective poison resulting in high performing catalysts in the dehydrogenation experiments with the LOHC system perhydro dibenzyltoluene/dibenzyltoluene (H18-DBT/H0-DBT). The Pt/TiO2 and S-Pt/TiO2 catalysts were compared to the current benchmarks Pt/γ-Al2O3 and S-Pt/γ-Al2O3. S-Pt/TiO2 was found to achieve a high degree of dehydrogenation of 98% which is competitive to the benchmark S-Pt/γ-Al2O3. In addition, analyses of the side products resulted in a higher selectivity toward dibenzyltoluene for S-Pt/TiO2 than for the γ-Al2O3 supported catalysts. Characterization with infrared spectroscopy (IR), transmission electron microscopy (TEM), and diffuse reflectance infrared Fourier transform spectroscopy with CO as adsorbing molecule (CO-DRIFTS) suggest the presence of strongly chemisorbed sulfur species as well as SMSI effects of the Pt/TiO2 catalysts. Based on kinetic studies, a batch and plug flow reactor for the dehydrogenation reaction were simulated for both titania supported catalysts. According to the calculations, the sulfur doped catalyst displays higher conversions in both batch and plug flow operation as compared to the unmodified system Pt/TiO2.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Catalytic dehydrogenation; Dibenzyltoluene; Liquid organic hydrogen carrier; Perhydro dybenzyltoluene; Reversible hydrogen storage; Selective poisoning